Review on the main differences between organic and conventional plant-based foods - Lima, Giuseppina Pace Pereira [UNESP]; Vianello, Fabio (Wiley-Blackwell Publishing, Inc, 2011)
P>The present review reports on the main characteristics and properties of plants cultivated following organic and conventional procedures, in the attempt to clarify give a deeper insight into some possible differences and to compare the two cultivation procedures. Here, we summarise research results regarding nutritional and safety properties of vegetable foods, evidencing qualitative differences observed between the two cultivation methods. It appears that the intake of organic foods leads to some advantages, such as the ingestion of a higher content of phenolic compounds and some vitamins, such as vitamin C, and a lower content of nitrates and pesticides. From literature, it appears that a special care should be taken about the ingestion of foods in relation to the content of some substances, e.g. polyamines, substances stimulating cellular division, because some foods coming from organic origin present a higher content of these compounds, which could explain some of the effect of the diet on patients affected by certain syndromes.
Keywords: Nutritional value; organic crops; pesticide residues; phenolic compounds; polyamines; safety issue